"Fast Simulation" in Evaluating Pilot/Aircraft Performance and Handling Qualities. Issue 32 (2016) - Hess, Ronald A.
Abstract: A pilot/vehicle analysis and simulation is exercised using a model of a large transport aircraft. The methodology allows overall handling qualities assessment and performance predictions in specific aircraft maneuvers. The pilot model is adaptive in nature with a goal of modelling pilot behavior in the face of sudden changes in flight control system characteristics. A multi-axis stability and command augmentation system is designed and its robustness is evaluated in a low-level landing approach flight condition. The simulation technique, referred to as fast simulation, shows promise as a preliminary tool prior to conducting pilot-in-the-loop evaluation.